Kedudukan dan Peranan Perempuan dalam Bidang Ekonomi Masa Bali Kuno Abad IX-XII Masehi - Sonia Asih, Ni Putu (Humanis, 2018)
This study focused on the data of ancient Balinese inscriptions IX-XII century AD , some of the female figures were mentioned . The emergence of these female figures has important capabilities and roles in government. The purpose of this study is to find out how the status and roles of women in the economic field in the period of the ancient Balinese IX-XII century AD. This study used several methods of data collection, data analysis and theories to answer the problems. Methods of data collection used were observation, literature study, and interview. In the next stage, it was processed by using qualitative analysis, contextual analysis, comparative analysis, and ethnoarkeolog y analysis. The theories used as the basis of reference in this research were the theory of postfeminism, functional structural theory and commercial development t h eory . The results of this study reveal that the status and role s of women in the economic field during the ancient Balinese century IX-XII AD is as crafters, farmers, artists, and as traders. The role s of women at that time is seen in various processes namely the process of production, distribution , and consumption.